Kant’s theory of self-consciousness - Gloy, Karen; Carlos (Estudios de Filosofía, 1991)
Properly speaking, there is no theory of self-consciousness in Kant, but there are elements leading to it, though problematic, due to their oscillating between a Cartesian past and a subsequent idealistic development. Such elements make part of the explanation undertaken by Kant of a system of objective knowledge. The structure of self-consciousness is that of a thinking self-relation: comprehensive, I-related or egologícal, spontaneously active and free, and self-reflective. The objective reference of self-consciousness guides Kant’s original critical philosophical problematic towards an idealistic philosophy.